Putting the Fe into Female Athletes: Insights into Heightened Iron Status and Women’s Australian Football Performance—A Case Study - Michael Pengelly; Kate Pumpa; David Bruce Pyne; Naroa Etxebarria (Sports)
Background: Iron deficiency affects up to 70% of female athletes, yet the effectiveness of improving iron status in team sport athletes remains unclear. Purpose: To evaluate the impact of variations in iron status on physical performance in elite female Australian Rules Football players. Methods: Iron status was measured in 30 players (age 23 ± 4 y; body mass 70 ± 6 kg) across three time-points of a 24-week season. Players identified as iron deficient non-anemic stage 2 in week 1 received an iron infusion. Remaining players were categorized into heightened iron status (FeUP; iron deficient non-anemic stage 1 players who were advised to take iron supplementation; n = 8) or non-supplemented (Ctrl; week 10: n = 17; week 24: n = 16) groups following week 10. Relative external load measures (e.g., total distance at different velocities), and strength and power measures (e.g., counter-movement jump, reactive strength index) were recorded in weeks 10 and 24 (same weeks as blood samples) to compare physical performance between FeUP and Ctrl groups. Results: Iron status improved in FeUP (30 µg/L to 49 µg/L) and reduced in Ctrl (39 µg/L to 34 µg/L) between weeks 10 and 24. Iron deficiency prevalence among all players was 47–54%. FeUp exhibited small to moderate improvements (5–19%) in some external load measures but no consistent improvement across all measures. At week 24, FeUP showed trivial to moderate differences outperforming Ctrl in seven physical performance measures (e.g., both hip adduction tests), but Ctrl outperformed FeUP in all other measures. Conclusion: Heightened iron status does not consistently enhance physical performance, although avoiding deficiency remains essential for athlete health.